PENGARUH MEDIA VIDEO TUTORIAL TERHADAP HASIL BELAJAR SISWA DALAM MATA PELAJARAN MENGGAMBAR SKETSA DI SMKN 4 PADANG - MAHIRIDHO AWALA, Drs. Wisdiarman, M.Pd., Yofita Sandra, S.Pd. M.Pd. (Universitas Negeri Padang, 2019)
The low score of students’ learning outcome in the sketch drawing subject at X grade of interior design is the crucial problem in this research. The purpose of this research is for knowing whether the tutorial video media gives anfabulous effect for students’ learning outcome in sketch drawing subject at X grade in SMKN 4 Padang.This research belongs to experiment research. The population of this research is all students of interior design class. The sample of this research is X DI A grade as the experiment class. A number of experiment class are 30 students. Besides, the control class of this research is X DI B class which can be classifed as the control class, with a number of students are 30 students too. In this research, the researcher chose purposive sampling as the technique of data collection. Both of the classes that had been stated clearly above are the places of conducting this research.After the researcher conducted the experiment by using tutorial video media, it gives the result as follows. Students’ learning outcome in experiment class and control class by using this tutorial video media actually are so different each other. In the experiment class, using the tutorial video media do not give too much positive impact for students’ learning outcome. In contrast, in the control class it can improve students’s learning outcome highly.Thus, the researcher sum up if by using this tutorial video media can give the significant impact highly for the students’ learning outcome. So that, the researcher recommends the school and also the teacher of interrior design for using this awesome tutorial video media in the teaching learning process.